Photophore counts in the deep-sea commercial shrimp Aristeus alcocki Ramadan, 1938 (Crustacea: Decapoda: Aristeidae), with a revised key to the Indo-West Pacific species of the genus - Chan, Tin-Yam; Kumar, Appukuttannair Biju; Yang, Chien-Hui (Zootaxa, 2017)
The availability of abundant fresh material of Aristeus alcocki Ramadan, 1938 from India allowed the evaluation of the variation in the numbers of photophores on the pereiopods in this species, as well as other diagnostic characters for species discrimination. Although the pereiopodal photophore counts in A. alcocki largely overlap with those of A. semidentatus Bate, 1888, it is found that A. alcocki is unique in the Indo-West Pacific species of the genus by the lower end of the cervical carina considerably farther away from the branchiostegal carina. Molecular genetic analysis confirmed the distinct taxonomic status of the six currently known species in this genus from the Indo-West Pacific and a revised key is provided for distinguishing them.